Global Development at a Pivotal Time - Kim, Jim Yong (2016)
World Bank Group President Jim Yong Kim discussed the priorities for the World Bank under his new leadership, including the immediate priority to help developing countries maintain growth and progress against poverty in these volatile economic times. The lesson of the last decade is that progress is possible for everyone. A great deal remains to be done. He sees four major challenges. The first is protecting development gains against global economic risks. The second is broadening development to countries that are being left out, especially so-called fragile and conflict states. The third is ensuring that growth is sustainable. The fourth is demanding that growth be inclusive. To broaden its partnerships, the Bank is creating a Global Partnership for Social Accountability. The Bank will hold itself accountable to the people it serves so that it is judged by results, not just intentions. Kim fielded questions on the role of government in development, civil society, social safety nets in crises, environmental and social sustainability, new instruments for problems in the global commons, clean energy projects, knowledge management, and the role of China.